Effects of statins on sarcopenia with focus on mechanistic insights and future perspectives - Zhang, Xianxu; Wang, Xianghong; Huang, Lei; Zhou, Changlin; Qian, Bin; Luo, Zhiqiang; Chen, Yanqiang (Frontiers in Pharmacology, 2025)
Sarcopenia is an age-related geriatric syndrome characterized by the progressive decline in skeletal muscle mass and function. Its pathogenesis is multifactorial, involving complex interactions between inflammatory responses, oxidative stress, and mitochondrial dysfunction. In recent years, statins, widely used as lipid-lowering agents, have garnered attention for their pleiotropic biological effects, particularly in their potential therapeutic value for anti-inflammatory, antioxidant, microcirculation improvement, and regulation of skeletal muscle metabolism. Statins have demonstrated promising potential in the prevention and treatment of sarcopenia. This review systematically examines the mechanisms through which statins act in sarcopenia, highlighting their pharmacological properties, biological effects, and relevant clinical and preclinical research advancements. Existing studies suggest that moderate statin use may improve the skeletal muscle microenvironment and maintain mitochondrial homeostasis by inhibiting the NF-κB signaling pathway, activating the Nrf2/ARE pathway, and modulating the AMPK/SIRT1/PGC-1α pathways. However, evidence also indicates that high doses or statin use in genetically predisposed individuals may result in mitochondrial dysfunction and muscle toxicity. Based on these findings, this paper proposes a “dose-mechanism-individual background” three-dimensional interaction model and further explores its potential synergistic or antagonistic effects when combined with exercise and nutritional interventions. Future research should prioritize conducting prospective clinical trials with stratified designs to develop individualized, precise intervention strategies, thus advancing the translational application of statins in managing muscle health in aging populations.